The effectiveness of cognitive behavioral therapy-based individual counseling in improving emotional regulation among students: a systematic literature review - Nelatu Fadila; Netrawati Netrawati; Afdal Afdal; Puji Gusri Handayani (Indonesian Institute for Counseling, Education and Theraphy, 2026)
Emotional dysregulation is a common problem among students and is associated with academic, social, and psychological difficulties. However, the effectiveness of individual counseling compared with group counseling or digital CBT-based interventions remains unclear. This systematic literature review followed the PRISMA 2020 guidelines to examine the role of individual counseling in improving students' emotional regulation. A structured Boolean search was conducted in the Scopus database using keywords related to cognitive behavioral therapy, individual counseling, emotional regulation, and student populations. The final search was completed in July 2026. Of 178 identified records, 163 remained after duplicate removal. Following screening and eligibility assessment, 10 studies met the inclusion criteria and were synthesized, supported by 40 additional Scopus-indexed references for theoretical and methodological discussion. The findings indicate that individual counseling generally improves emotional regulation, although its effectiveness varies according to the therapeutic relationship, mental health comorbidities, delivery format, cultural context, developmental stage, and participant characteristics. Complementary approaches, including music-based and technology-assisted interventions, may further enhance emotional regulation beyond traditional counseling. These findings strengthen transdiagnostic and mechanism-based CBT perspectives while providing practical implications for school counselors and clinicians to prioritize emotional regulation skills alongside symptom reduction. The review was limited by the small number of eligible studies and heterogeneous outcome measures. Future research should directly compare individual and group CBT formats using standardized emotional regulation measures and longer-term, cross-cultural designs.